A COMPARATIVE STUDY ON COPYRIGHT PROTECTION FOR DIGITAL WORKS IN PALESTINE AND UK - Mohammed M.M Qtait; Mohammed Nizam Awang; Haliza A. Shukor; Intan Nadia Ghulam khan (Journal of Islamic Management Studies, 2024)
The direct influence of technology on copyright was the main impetus for the development of copyright legislation. Because the Palestine Copyright Act of 1911 is out of date, it does not address the technological advancements in copyright field. The state of Palestine drafted a proposal for new copyright legislation that governs the copyright protection for digital works, but owing to the suspension of the parliament, it has not been enacted. This research aims to examine issues of the meaning of digital copyright works, the requirements for copyright protection for digital works, copyright protection for digital works that described in the Palestine Copyright Act of 1911, the Palestine Copyright Draft (Proposal) 2013, and UK CDPA 1988 in order to strengthen a substantial component of the law in Palestine. The comparative research approach was used, along with a functional method. The findings of this research indicate that the Palestine Copyright Act 1911 lacks copyright protection for digital works, while the Palestine Copyright Draft 2013 governs this issue to some extent. This study suggests that before the copyright draft is approved, changes need to be made, especially in regard to the issue of copyright protection requirements.